STRATEGI KREATIF PERANCANGAN KOMUNIKASI VISUAL PARIWISATA INDONESIA “TEMUKAN LOKALMU” - Iskandar, Bianca; Valentina, Anny; Bekti, Siti Nurannissaa Parama (Jurnal Bahasa Rupa, 2021)
As a country known for its diversity of natural beauty and cultural diversity, Indonesia has the potential as a tourist destination. Tourism is one of the largest income in Indonesia. The high interest of foreign tourists is inversely proportional to the decrease of local tourists every year. One of the reasons is that local tourists prefer to travel abroad. Pandemic conditions are also one of the causes of declining in the domestic tourism industry. This study aims to find an alternative concept of creative strategies for designing tourism visual communication that emphasizes local aspects. This research used mixed methods, quantitative methods by using questionnaires and qualitative methods by using observation, interviews and literature study. The target audience is the young generations aged 21-27 years, domiciled in Jakarta and having SES A-B economy class. The result of this research form a creative strategy in visual communication design with the concept of "Discover your locale". This concept emphasizes the delivery of information about characteristics, local aspects, and recommended information on the attractiveness of an area from local residents to gain new experiences.